(untitled) (Conferencea, 2024)
Oxidative stress causes an imbalance between the oxidation and antioxidant systems of mitochondria. Active forms of oxygen (reactive oxygen species - ROS) and reactive nitrogen species can be harmful or beneficial for cells. An increase in the concentration of free radicals changes the conductance value of mitochondrial ion channels. One such ion transport system is ATP-dependent potassium channel (mitoKATP-channel) located in the inner membrane of mitochondria [1; 2]. Most of the drugs available today target mitochondrial ion channels [3]. Under conditions of oxidative stress, the damage in mitochondria can be corrected by biologically active substances. Currently, intensive scientific research is being conducted in this regard. However, no studies have been conducted on changes in the activity of cardiac mitoKATP-channel in rats under conditions of oxidative stress and the effect of 1-(4-methoxyphenyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline (F-4) alkaloid on them.